2017
DOI: 10.3389/fmars.2017.00218
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing and Quorum Quenching in the Mediterranean Seagrass Posidonia oceanica Microbiota

Abstract: Posidonia oceanica (L.) Delile is an endemic Mediterranean seagrass angiosperm. The taxonomic diversity of the Posidonia-associated microbiota has previously been inventoried using culture-based and culture-independent approaches. However, little is known about the type of chemical interactions that occur between the cells within this microbiota. In this study, we isolated 60 bacterial strains from the leaves and rhizomes of P. oceanica and evaluated their capacity to communicate through quorum sensing. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…QQ might be another important process for the adaptation of Rm01 to marine particles. Previous studies demonstrated that many strains capable of AHL interference have been isolated from sediments, biofilms, the surface of the alga Fucus vesiculosus (Romero et al, 2012) and the Mediterranean seagrass angiosperm Posidonia oceanica (Blanchet et al, 2017), and marine particles (Table 1) in which QS activity is easily concentrated. The QQ processes in dense microbial niches limit the coordination of antagonistic bacteria and even affect vital activities of their phytoplankton host (Tait et al, 2009; Rolland et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…QQ might be another important process for the adaptation of Rm01 to marine particles. Previous studies demonstrated that many strains capable of AHL interference have been isolated from sediments, biofilms, the surface of the alga Fucus vesiculosus (Romero et al, 2012) and the Mediterranean seagrass angiosperm Posidonia oceanica (Blanchet et al, 2017), and marine particles (Table 1) in which QS activity is easily concentrated. The QQ processes in dense microbial niches limit the coordination of antagonistic bacteria and even affect vital activities of their phytoplankton host (Tait et al, 2009; Rolland et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…2. Remarkably, these bacteria have been described to be associated with Rhodophyta and Embryophyta algae (19,20) and with nine animal phyla, including more than 15 different sponge genera. In fact, in more than half of the 134 studies here considered, Pseudovibrio spp.…”
Section: Distribution Of Bacteria Belonging To the Pseudovibrio Genusmentioning
confidence: 99%
“…From this collection, we were able to detect 6 strains able to emit 8 different types of AHLs and 19 strains able to activate the AI-2 biosensors. These results reveal the importance of examining quorum sensing relationships also within the microbiota of marine angiosperms to better understand the complex relationships that may exist between these microbes and their host (Blanchet et al, 2017).…”
Section: A Phycosphere Of (Micro)-algae and Phyllosphere Of Marine Pmentioning
confidence: 96%